Raman Studies of Carbon Nanostructures - Jorio, Ado; Souza Filho, Antonio G. (Annual Review of Materials Research, 2016)
This article reviews recent advances on the use of Raman spectroscopy to study and characterize carbon nanostructures. It starts with a brief survey of Raman spectroscopy of graphene and carbon nanotubes, followed by recent developments in the field. Various novel topics, including Stokes–anti-Stokes correlation, tip-enhanced Raman spectroscopy in two dimensions, phonon coherence, and high-pressure and shielding effects, are presented. Some consequences for other fields—quantum optics, near-field electromagnetism, archeology, materials and soil sciences—are discussed. The review ends with a discussion of new perspectives on Raman spectroscopy of carbon nanostructures, including how this technique can contribute to the development of biotechnological applications and nanotoxicology.
Keywords: Raman spectroscopy